2016
DOI: 10.1007/s00240-016-0911-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for urolithiasis in patients with ankylosing spondylitis: a prospective case–control study

Abstract: It has been reported that renal stone formation increased in patients with ankylosing spondylitis (AS). However, its reason remains unclear. The aim of this study was to evaluate serially the possible risk factors for renal stone formation in AS patients. Two groups consisted of AS patients with renal stone (n = 30), AS patients without renal stone (n = 30), and 20 healthy controls (HC) were included to the study. Parathyroid hormone, calcium, magnesium, phosphorus and immunoglobulin A levels and 24 h urine we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…Although this study did not reach statistical significance, the authors also found high urinary calcium levels compared to patients who did not have calculi. They concluded that a subgroup of AS patients tend to have high blood and urinary calcium and that these biochemical abnormalities and other factors might be responsible for the development of urolithiasis [11]. Our study was not in line with their trial as we could not find any significant difference in the blood level of calcium, phosphorus, Vitamin D, parathormone, and urinary calcium excretion.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Although this study did not reach statistical significance, the authors also found high urinary calcium levels compared to patients who did not have calculi. They concluded that a subgroup of AS patients tend to have high blood and urinary calcium and that these biochemical abnormalities and other factors might be responsible for the development of urolithiasis [11]. Our study was not in line with their trial as we could not find any significant difference in the blood level of calcium, phosphorus, Vitamin D, parathormone, and urinary calcium excretion.…”
Section: Discussioncontrasting
confidence: 86%
“…Here with the pathologi- cal process of resorption, the predominance of formation phase in the bone cycle could also affect the formation of renal calculi [24]. In a recent prospective study, Gonullu et al found a significantly higher level of blood calcium at the baseline in AS patients with compared to AS patients without renal calculi [11]. Although this study did not reach statistical significance, the authors also found high urinary calcium levels compared to patients who did not have calculi.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…We previously found that suppression of the NF‐κB signal reduces the risk for crystal formation in human renal tubular cells . In addition, although the relationship between kidney stone formation and the role of immunoglobulins is not well understood, the correlation between immunoglobulin A and the risk of urolithiasis, as well as a possible immunoglobulin treatment for atherosclerosis, have been reported …”
Section: Discussionmentioning
confidence: 99%